Potential renewable energy resources of the Lerma Valley, Salta, Argentina for its strategic territorial planning - Belmonte, Silvina (2009)
Renewable energy sources are considered as strategic opportunities to improve the population’s quality of life, to promote the development of more efficient and equitable economic systems, and to favor environmental sustainability in the territorial planning of Lerma Valley (Salta, Argentina). The mapping in raster format (each pixel having a reference value) of the potential renewable energy sources (solar, wind, biomass, hydraulic, mixed) is essential to define ideal locations for different types of renewable applications, and to plan suitable strategies for its implementation. It is necessary considering environmental diversity and site conditions (topographic, natural resource, infrastructure and service availability, social and economical) of the intervention area. Different methodologies are used for mapping of potential energy resources. Solar radiation is spatialized through the application of statistical regressions between altitude, latitude, precise incident solar radiation records, and radiation data estimated with the Geosol V.2.0.™ software. The Argentina Map program is used for the wind potential resource modeling. It requires as inputs: a Digital Elevation Model, a land use and cover map (to determine roughness), and measured and/or estimated wind speed and frequency data. The hydroelectric potential for microturbine applications is calculated from the topographic drop and the annual mean flow in cumulative models, through the application of the Idrisi Kilimanjaro™’s runoff tool; while the power densities are compared at the watershed. Biomass potential (at this exploratory stage), is interpreted from the available biomass type (land use and cover map), its energy application availability, and some quantitative indicators associated with the biomass types identified as priority. In conclusion, the renewable energy potential in Lerma Valley is very high and diverse, and its close connection with social–environmental conditions is basic for the creation of energy resource-related territorial plans.